South Asian Animal Divination : A Critical Anthology - Zysk, Kenneth G. (Asian Studies E-Books Online, Collection 2025., 2025)
This scholarly work examines the history and practice of animal omen divination in South Asia, comparing it to similar traditions in Mesopotamia and classical antiquity. It provides critical editions and translations of relevant texts, including chapters from the Gārgīyajyotiṣa , Śārdūlakarṇāvadāna , and the Bṛhatsaṃhitā , focusing on the interpretation of bird calls and behaviour. The study incorporates ornithological and natural historical information to enhance the understanding of the omens and their regional origins. Furthermore, it explores the evolution of omen literature and the transmission of knowledge across cultures and time periods, highlighting the enduring significance of sound and direction in divination practices.